Evolución del sector de la construcción y su incidencia en el crecimiento económico de Ecuador, en el período 1990 – 2020 - Hernández Granda, Joyce Jessenia (2022)
The construction sector is a dynamic element of the economy. However, according to the Central Bank (2020), the construction sector suffered a significant drop of 14.2% in the third quarter of 2020 and is expected to decrease 1.2% in 2021. We propose policies to boost economic growth through the statistical and econometric analysis of the construction sector on the economic growth of Ecuador in the period 1990-2020. The data is from the Central Bank of Ecuador (2020), and the statistical data from the World Development Indicators (WDI) for the period 1990-2020. The econometric strategies used were based on Granger causality and cointegration tests for time series. The main results show that there is a direct relationship between the GVA of construction and economic growth, in addition, the long-term balance between the GVA of construction and economic growth and bidirectional causality in the sense of Granger are emphasized. Given these scenarios, the State proposes to increase investments in infrastructure, as well as policies to achieve macroeconomic stability, which contribute to increasing the purchasing power of apartment buyers and public investments, while encouraging the employment of labor of the construction companies.